Fabrication of β-cyclodextrin modified mesostructured silica coated multi-walled carbon nanotubes composites and application for paraben removal - Ding, Chuyuan; He, Jun; Xu, Mengxia; Wang, Chengjun (IWA, 2018)
In this work, the novel β-cyclodextrin modified mesostructured silica coated multi-walled carbon nanotubes (MWCNTs) composites were synthesized and applied for the removal of parabens in aqueous solution. The prepared MWCNTs/SiO2/β-CD composites were characterized by Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy and thermogravimetric analysis. The effects of the amount of adsorbent, pH and elution solvents on the removal efficiency of parabens from water solutions were investigated. Under the optimized conditions, over 95% removal efficiency was achieved by using 40 mg of MWCNTs/SiO2/β-CD adsorbents to absorb the parabens from 60 mL of 0.5 μg/mL parabens solutions. The solution pH in the range from 5 to 9 has no influence on the removal efficiency and the parabens sorption capacity of the prepared adsorbents were around 0.75 μg/mg. Furthermore, the stability and reusability studies demonstrated that the prepared MWCNTs/SiO2/β-CD composites are cost-effective adsorbents for the removal of parabens from water with high regeneration efficiency. The composites fabricated in this study could become an attractive candidate for water purification.